Modern Japanese thought - Wakabayashi, Bob Tadashi (Cambridge University Press, 1997)
Over the past two centuries, Japan has undergone Westernization not only in the external realm of material culture and sociopolitical organization, but also in the inner realm of thought and morals. This comprehensive intellectual history, consisting of chapters from volumes five and six of the Cambridge History of Japan, plus a new introduction and chapter on postwar intellectual trends, describes the forces that made Japanese thinkers both receptive and hostile to Western ideas and values from the 1770s to the 1990s. Important themes in the book are the potential of Western learning to discredit as well as bolster the existing order, and the perennial tension between indigenous and alien, traditional and modern, and rulers and ruled. More specific topics include: Japan's turn to the West; the Meiji Enlightenment and enthusiasm for Westernization; the mid-Meiji conservative reaction; socialism and nationalism in the prewar years; the shock of defeat; and the growth of democracy since 1945.